2014
DOI: 10.1063/1.4870997
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene mixtures enhance the thermal stability of a non-crystalline polymer solar cell blend

Abstract: Printing of polymer:fullerene solar cells at high speed requires annealing at temperatures up to 140 °C. However, bulk-heterojunction blends that comprise a non-crystalline donor polymer often suffer from insufficient thermal stability and hence rapidly coarsen upon annealing above the glass transition temperature of the blend. In addition, micrometer-sized fullerene crystals grow, which are detrimental for the solar cell performance. In this manuscript, we present a strategy to limit fullerene crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 25 publications
0
53
0
Order By: Relevance
“…This observation may be explained by the reduced tendency of fullerenes to crystallize upon mixing, which is well documented for substituted fullerenes (PCBMs) and leads to the formation of disordered thin films. [15][16][17] We note that as a result of improved film formation…”
Section: / 18mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may be explained by the reduced tendency of fullerenes to crystallize upon mixing, which is well documented for substituted fullerenes (PCBMs) and leads to the formation of disordered thin films. [15][16][17] We note that as a result of improved film formation…”
Section: / 18mentioning
confidence: 99%
“…This observation may be explained by the reduced tendency of fullerenes to crystallize upon mixing, which is well documented for substituted fullerenes (PCBMs) and leads to the formation of disordered thin films. [15][16][17] We note that as a result of improved film formationFETs based on fullerene mixtures allow for greater reproducibility. The FET device characteristics are largely independent of the fullerene ratio with a threshold voltage ℎ ~ 6-7…”
mentioning
confidence: 99%
“…[26,27] Furthermore, it was shown that mixtures of different fullerenes can improve the thermal stability of BHJs. [28][29][30][31][32] Despite an intense research, known techniques to stabilize BHJs either reduce only partially thermal degradation or produce poor device efficiencies. So it is a primary challenge for processing of thermally stable fullerenebased high-efficiency PSCs to identify novel strategies for inhibiting fullerene diffusion inside BHJs.…”
Section: Introductionmentioning
confidence: 99%
“…12 Another promising concept to reduce degradation in fullerene-based solar cells is the use of third components which can improve the mechanical, photo, air and thermal stability of organic solar cells. 13 Such third components can be crosslinkers, [14][15][16] conventional fullerenes, [17][18][19] modified fullerene derivatives, [20][21][22] compatibilizers 23,24 or insulating polymers. 25 In this work, we overcome the aggregation of the fullerene acceptor PC 61 BM during thermal annealing by employing ternary D-D-A blends comprising two commercially available donor polymers.…”
Section: Introductionmentioning
confidence: 99%